Analisis Pengadaan Cek Tarif Dan Pembayaran Reklame Dalam Upaya Meminimalisir Pelanggaran Izin Di Kota Probolinggo Tahun 2024 (Studi Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Probolinggo) - Supriyanto, Supriyanto; Yunus, Eko Yudianto; Hasan Akbar, Mohammad (Universitas Jabal Ghafur, 2025)
This study aims to analyze the process of procuring tariff checks and advertising payments in an effort to minimize advertising permit violations in Probolinggo City in 2024. The focus of the study is directed at the role and mechanisms carried out by the Probolinggo City Investment and One-Stop Integrated Service Agency (DPMPTSP) in supervising and enforcing advertising licensing regulations. The method used in this study is a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the procurement of tariff checks and advertising payment systems has made a positive contribution to increasing business actors' compliance with advertising licensing. However, several obstacles were still found, such as lack of socialization, limited human resources, and weak supervision in the field. Therefore, it is necessary to strengthen the digitalization system of services and improve coordination between related agencies in order to reduce the number of advertising permit violations in the future.Keywords: Tariff check, advertising payment, permit violation, licensing